Cinema the first hundred years - Shipman, David (New York St. Martin's Press, 1993)
On February 1, 1893, Thomas Alva Edison completed the first motion picture studio: a hut on a pivot that could be rotated to follow the sun. Almost a year later, on January 7, 1894, he took a copyright for the very first film - a memorable short entitled Fred Ott's Sneeze. And from these inauspicious beginnings, one hundred years later, has grown a medium that is arguably the most popular and influential man has created David Shipman, for decades on of the world's leading film critics and historians, has in Cinema: The First Hundred Years given us a definitive survey of film's first century - and one of the most lavishly illustrated volumes on cinema history ever produced. With profound expertise, sharp wit and unmatched insight, Shipman chronicles the medium's watershed events, year by year - great stars discovered, classic films released, gala openings celebrated, Oscars awarded, accepted, and declined. Here in the 1907, sixteen-scene version of Ben Hur: the classics of the 1930s and 1940s, from Gone With The Wind and Casablanca to David Copperfield and The Bride of Frankenstein: here are the Cinemascope extravaganzas of the 1950s, the road movies of the 1960s, and the modern classics of today. Shipman's scope is exhaustive; the 2,500 films covered include hundreds of international films as well as Hollywood pictures. Accompanying Shipman's text is a photographic record unequalled in its quality: not just another compendium of familiar stills. Cinema resurrects hundreds of pristine, museum-quality photos from archives around the world, reproducing them in a striking oversize format that recalls the grandeur of moviegoing at its most memorable. Complementing Shipman's verbal survey with a gallery of unforgettable visual images, this is a one-of-a-kind volume: the next century is not likely to see a more rewarding gift for the film fan of any age.
Includes index.
Keywords: Motion pictures -- History